Experimental study on the nucleate boiling heat transfer characteristics of a water-based multi-walled carbon nanotubes nanofluid in a confined space. (October 2017) - Xia, Guodong; Du, Mo; Cheng, Lixin; Wang, Wei
Highlights: The MWCNTs nanofluids boiling in a confined space at a sub-atmospheric pressure. Visualization of the boiling processes using a high-speed video camera. Effects of the surfactant, the MWCNTs and heat flux on the boiling behaviors. Exploring the roughness and contact angle of the MWCNTs deposition. Analysis the mechanisms of the heat transfer enhancement of the MWCNTs nanofluids. Abstract: Experimental investigation of nucleate boiling heat transfer of a water-based multi-walled carbon nanotubes (MWCNTs) nanofluid in a confined space is presented in this study. First, the effects of four different surfactants on the stability of the nanofluids were investigated and the suitable surfactant gum acacia (GA) was selected for the boiling experiments. Then, the boiling experiments of the nanofluids with various volume fractions (0.005–0.2%) of the MWCNTs were conducted at a sub-atmospheric pressure of 1 × 10 −3  Pa and the test heat fluxes are from 100 to 740 kW/m 2 . Furthermore, GA with four different mass fractions was respectively dissolved in the nanofluids to investigate the effect of the GA concentration on the boiling heat transfer. The effects of the heat flux, the concentrations of the MWCNTs and surfactants, the bubble behaviors and the surface conditions after the boiling processes have been analyzed. The results show that the MWCNTs nanofluid can enhance boiling heat transfer as compared to the base fluid. This is mainly caused by the nanoparticles deposition on the boiling surface result in increasing the surface roughness and reducing surface contact angle. It is also found that addition of GA can inhibit the deposition of the nanoparticles but may reduce the boiling heat transfer coefficient of the nanofluids. According to the experimental results, the maximum heat transfer coefficient enhancement ratio can reach 40.53%. It is also noticed that the heat transfer enhancement ratio decreases with increasing the heat flux at lower heat fluxes from 100 to 340 kW/m 2 while it increases with increasing the heat flux at higher fluxes from 340 to 740 kW/m 2 . At the lower heat fluxes, the deposition layer increases the frequency of bubble formation and thus the boiling heat transfer is strengthened. While at the high heat fluxes, the increasing heat flux may strengthen the capability of the nanoparticles deposition and the disturbance of the nanoparticles and increase the enhancement ratio of heat transfer coefficient.